Identification of Fur in Pasteurella multocida and the Potential of Its Mutant as an Attenuated Live Vaccine - Liu, Qing; Hu, Yunlong; Li, Pei; Kong, Qingke (Frontiers in Veterinary Science, 2019)
Pasteurella multocida (P. multocida) is a pathogenic microorganism that causes a variety of serious diseases in humans and animals worldwide. The global regulator gene, fur, plays an important role in pathogenesis and regulates the virulence of many bacteria. Here, we identified a fur gene in P. multocida by complementing a Salmonella Choleraesuis Δfur mutant, and characterized a fur mutant strain of P. multocida. The P. multocida Δfur mutant strain exhibited no significant differences in growth and outer membrane protein (OMP) profiles when the complemented strain was compared to the parent. Ducks were used as the model organism to determine the virulence and protection efficacy induced by Δfur mutant strain. Animal experiments showed that colonization by the mutant was decreased by oral infection of live Δfur mutant strain. The LD50 of the ducks infected with the Δfur mutant was 146-fold higher than that of the ducks infected with the wild-type strain when administered through the oral route. Evaluation of the immunogenicity and protective efficacy of the Δfur mutant of P. multocida revealed strong serum IgY and bile IgA immune responses following oral inoculation with the Δfur strain. Ducks that were orally inoculated with the Δfur mutant strain demonstrated 62% protection efficacy against severe lethal challenge with the wild-type P. multocida. This study provides new insights into P. multocida virulence and the potential use of an attenuated vaccine against P. multocida.